Resistant Soil Microbial Communities Show Signs of Increasing Phosphorus Limitation in Two Temperate Forests After Long-Term Nitrogen Addition - Forstner, Stefan J.; Wechselberger, Viktoria; Stecher, Stefan; Müller, Stefanie; Keiblinger, Katharina M.; Wanek, Wolfgang; Schleppi, Patrick; Gundersen, Per; Tatzber, Michael; Gerzabek, Martin H.; Zechmeister-Boltenstern, Sophie (Frontiers in Forests and Global Change, 2019)
Forest soils harbor diverse microbial communities responsible for the cycling of elements including carbon (C), nitrogen (N), and phosphorus (P). Conversely, anthropogenic N deposition can negatively feed back on soil microbes and reduce soil organic matter (SOM) decomposition. Mechanistically, this can include reductions of decomposer biomass, especially fungi, and decreases in activities of lignin-modifying enzyme (LMEs). Moreover, N inputs can lower resource C:N and thus decrease the C:N imbalance between microbial decomposers and their resources. As a result, microbially-mediated decomposition might slow down, resulting in larger SOM pools with consequences for ecosystem nutrition and climate regulation. Here, we studied the long-term impact of experimental N addition on soil microbes and microbially-mediated decomposition in two coniferous forests in Switzerland and Denmark. We measured microbial biomass C and N, phospholipid fatty acid (PLFA) biomarkers and potential enzyme activities related to C, N, and P acquisition along the topsoil profile (0–30 cm). In particular, we investigated shifts in microbial C:N homeostasis and relative C:N:P limitation. Contrary to prevailing theory, microbial biomass and community composition were remarkably resistant against two decades of 750 and 1,280 kg ha−1 of cumulative N inputs at the Swiss and Danish site, respectively. While N reduced fungal-specific PLFAs and lowered fungi-to-bacteria (F:B) ratios in some (mainly organic) horizons where soil organic carbon (SOC) has accumulated, it increased F:B ratios in other (mainly mineral) horizons where SOC has declined. We did not find a consistent reduction of LME activities in response to N. Rather, relationships between LME activities and SOC concentrations were largely unaffected by N addition. This questions prevalent theories of lignin decomposition and SOC storage under elevated N inputs. By using C:N stoichiometry, we further show that microbial communities responded in part non-homeostatically to decreasing resource C:N, in addition to a likely increase in their carbon use efficiency and a decrease in nitrogen use efficiency. While the expected increased allocation to C- and decreased allocation to N-acquiring enzymes was not found, microbial investment in P acquisition (acid phosphatase activity) increased in the nutrient-poor Podzol (but not in the nutrient-rich Gleysol). Enzyme vector analysis showed decreasing C but increasing P limitation of soil microbial communities at both sites. We conclude that simulated N deposition led to physiological adaptations of soil microbial communities across the topsoil profile in two independent experiments, with long-term implications for tree nutrition and SOC sequestration. However, we expect that microbial adaptations are not endless and may reach a tipping point when ecosystems experience nitrogen saturation.